Pesantren dan Pendidikan Perdamaian - Masamah, Ulfa (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2013)
Surakarta was a city which had high intensity of religious social conflict that has to be managed as well as possible, transformed, and developed a peace. This research is about the roles of Pesantren of Al Muayyad Windan in which its capability to transform the conflict in Surakarta. The research findings showed that religious conflict transformation that could be done and based on the principle of the admission existence and the empowerment existence. The principles were based on the theology that was percepted and become as the motivation to do social changes, and developed the transformative Islam unto the multiculturalism.